GOBIERNOS Y POLÍTICAS: TRANSFORMACIONES EN ARGENTINA Y AMÉRICA LATINA EN LA PRIMERA DÉCADA DEL SIGLO XXI - Hintze, Susana (Universidad de Costa Rica, 2013)
During recent years, innovative national political processes have developed in Latin American. These processes are characterized by the emergence of new forms of organization and for social practices and governments that challenge the neoliberal order. This article aims to discuss the emerging conditions and the characteristics of these new governments. Furthermore, it analyzes policies implemented by these governments in terms of similarity/dissimilarity with the ones implementing during neoliberal period, as well as, their changes and tensions.